The Importance of Early Childhood Education (Modern education and development, 2024)
This article extensively analyzes the impact of early childhood education on child development. It examines the psychological, social, and emotional aspects of the educational process and how it influences children's future success. Additionally, it provides critical insights into the significance and development potential of this period within the modern education system.